The Neuroprotective Effects of Germinated Black Glutinous Rice Diet on Aβ25-35 Peptide Induced Learning and Memory Deficits in Male Rats - Pramoolsilpa, Gayvalin; Nudmamud-Thanoi, Sutisa; Khongsombat, Onrawee (Journal of Basic and Applied Pharmacology, 2017)
Germinated black glutinous rice (GBGR) is a black glutinous rice (BGR) that has been soaked in water to initiate pre-germination. It is also known as pre-germinated brown rice (PGR). Important nutrients in GBGR are γ-aminobutyric acid (GABA), γ-oryzanol, and other bioactive lipids. GABA concentrations in GBGR are more than 15 times greater than in non-germinated rice. PGR has been reported to have neuroprotective effects in developing rats against the accumulation of lead and protects against neuronal cell loss and memory deficits, but there has been no such report regarding GBGR. We therefore investigated the effects and protective mechanisms of GBGR against Aβ25-35 peptide induced neurotoxicity in rats. In our in vivo studies, rats were fed with control, BGR, and GBGR diets throughout the experiment and were injected intraventricularly with 15 μL of aggregate Aβ25-35 peptide on day 22. The effects on locomotor activities were evaluated by open field test, spatial navigation and recognition memory by Morris water maze and novel object recognition tests, respectively. Glutamate and GABA concentrations were analyzed by high performance liquid chromatography with electrochemical detection. Finally, the neuronal viability was counted by histological techniques. The results showed that rats given GBGR significantly increased spatial and recognition memory and increased GABA concentration in the hippocampus. Moreover, GBGR also improved neuronal viability. It can be concluded that GBGR has a potential role to protect against memory deficits in an Alzheimer’s rat model.